FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - SUARYANA, AGUNG (Jurnal Ilmiah Akuntansi dan Bisnis, 2012)
Social and environmental responsibility has become one of disclosure component required for listing on Indonesia Stock Exchange (BEI). Disclosure is done on annual or sustainability report. This research examine factors influencing policy of social and environmental responsibility disclosure of manufacturers listed on BEI by expanding disclosure items. The disclosure items was identified based on Reporting Guidelines stated on the General Reporting Initiatives (GRI). Seventy nine items of disclosure were obtained. Factors expected to influence social and environmental disclosure policy are leverage, profitability, size of commissioner board, size of company, and managerial ownership. Sample consists of manufacturers disclosing social and environmental responsibility during 2007-2009 with 75 observations. The policy was measured by disclosure index on Reporting Guidelines as stated on General Reporting Initiatives (GRI). Hypotheses were tested using multiple regression. The result fails to support influence of leverage, profitability, size of commissioner board, and managerial ownership on social and environmental disclosure. Company size is the only factor to influence the disclosure, so it supports company size hypothesis in positive accounting theory.
Keywords: social and environmental responsibility disclosure, General Repoting Initiatives